Which medications are safe and effective for improving sleep at high altitude? - Luks, A. M. (High Altitude Medicine & Biology, 2008)
Given the well-established problems with sleep at high altitude, it is not uncommon for people planning trips to the mountains to seek advice from clinicians regarding pharmacologic options for improving sleep during their trip. This review article considers the various medications that have been studied for this purpose at high altitude with an emphasis on both their efficacy and safety. The available data support the use of either acetazolamide, temazepam, zolpidem or zaleplon in this environment. Other agents commonly used at sea-level such as eszopiclone and diphenhydramine have not been studied at high altitude but are likely safe to use given their mechanism of action and known side effects. Limited evidence suggests diazepam may cause hypoventilation at high altitude and its use in this environment should be discouraged. Insufficient data exist to determine which agent is most effective at altitude nor do we know whether combination therapy with acetazolamide and a hypnotic agent offers any benefits over monotherapy.